Nano‑enabled pesticides: a comprehensive toxicity assessment of tebuconazole nanoformulations with nematodes at single species and community level - Eghbalinejad, Mahleh; Hofman, Jakub; Kotouček, Jan; Grillo, Renato [UNESP]; Bílková, Zuzana Hochmanová; Reiff, Nicola; Höss, Sebastian (Springer Nature, 2024)
There is an increasing imperative to explore safer alternatives for pesticides due to their indiscriminate use and consequential health impacts on the environment and humans. Nanoformulations of pesticides are being developed as potential alternatives due to their beneficial properties, including enhanced solubility, targeted delivery to the site of action, improved stability and efficacy and reduced non-target effects. Nevertheless, a comprehensive assessment is necessary for these emerging nanopesticides compared to existing formulations, aiming to ascertain whether their "nano" characteristics exacerbate toxicity for non-target organisms. This study investigated the toxicity of tebuconazole (TBZ) in different formulations, including nanoformulations (poly-ε-caprolactone [PCL] and nanostructured lipid carrier [NLC] loaded with TBZ), as well as a commercial formulation, on the reproduction of the nematode Caenorhabditis elegans in both aqueous and soil matrices. Additionally, the impact of the correspondent nanocarriers without TBZ on C. elegans was examined. In water, TBZ in the form of nano and commercial formulations exhibited higher toxicity on the nematodes’ reproduction than the TBZ (a.s.) attributable to higher freely dissolved concentrations of TBZ, which resulted in a toxicity order, ranging from the most to the least toxic as follows: NLC-TBZ > PCL-TBZ > commercial formulation > TBZ (a.s.). For NLC-TBZ, the excess toxicity could be clearly explained by combined toxicity of TBZ (a.s.) and nanocarriers, with the effect addition of the separate single compounds matching the observed effects of the nanoformulation. For PCL-TBZ, effects were stronger than expected from the effect addition of TBZ (a.s.) and PCL nanocarriers, potentially due to enhanced bioavailability of encapsulated TBZ in the gut of the nematodes. In soil, NLC with and without loaded TBZ showed higher toxicity than other tested compounds, while PCL nanocarriers without TBZ did not exhibit negative effects on the reproduction of C. elegans. Microcosm experiment, where longterm effects on native soil nematode fauna were tested, confirmed that TBZ-nanoformulations act via combined toxic effects of TBZ and nanocarriers. These findings contribute valuable insights to understanding nanopesticides’ ecotoxicity and underscore the need for harmonized regulatory assessments to evaluate these novel formulations adequately.
Nanopesticidas: uma avaliação abrangente da toxicidade de nanoformulações de tebuconazol com nematóides em uma única espécie e em nível comunitário
Keywords: Combined toxicity; Nanotoxicity; Caenorhabditis elegans; Microcosm; Poly-ε-caprolactone; Tripalmitin